Promoting Global Citizenship Education in Language Programs - Aljuaid, Hind (Advances in Social Sciences Research Journal, 2021)
This paper will discuss tools and methods of how to integrate global citizenship education in language programs to facilitate students’ knowledge and development as responsible global citizens. Developing global citizens requires a theoretical foundation, applied learning, and identification of transferrable skills. The paper will provide students and educators with the necessary tools for fostering cross-cultural knowledge, global issues and mind-set to become culturally conscious participants in a global community. The paper will discuss how these teaching practices can be developed alongside disciplinary learning goals in language courses and course content within the curriculum. Finally, the paper will discuss the implications of implementing these practices for language programs and how they will help in understanding how students enact the idea of fostering global competency and deciphering pedagogical tools that lead students to meaningful learning and engagement.